Mediation in Medical Disputes as a Pathway to Substantive Justice: Reframing Global Health Law through Human-Centered Dispute Resolution: Mediation in Medical Disputes as a Pathway to Substantive Justice: Reframing Global Health Law through Human-Centered Dispute Resolution - Raymond Nadeak; Risma Situmorang; Supaphorn Akkapin (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
Medical disputes are increasingly common worldwide as patients become more aware of their rights and healthcare providers face stricter professional standards. Conventional litigation, while ensuring procedural justice, often fails to address the ethical, moral, and psychological aspects of medical conflicts. This research highlights a key gap in the literature: the limited recognition of mediation not just as a cost-effective alternative but as a tool for achieving substantive justice. Using a qualitative normative approach, this study combines doctrinal and comparative analyses. Findings show that mediation resolves disputes more efficiently than litigation and at much lower costs. Beyond efficiency, mediation improves access and delivers substantive justice by addressing patients’ emotional needs, rebuilding trust, and maintaining professional integrity. However, challenges still exist, including limited legal recognition of mediation outcomes, a shortage of specialized mediators, and cultural resistance favoring litigation. This study contributes theoretically by reframing mediation as a justice-oriented process aligned with restorative justice and practically by offering policy suggestions to strengthen mediation’s legitimacy and institutional role in global health governance. Therefore, mediation should be recognized not only as an alternative procedure but as a key instrument for substantive justice within international health law.